Training load characteristics and injury and illness risk identification in elite youth ski racing: A prospective study - Hildebrandt, C.; Oberhoffer, R.; Raschner, C.; Müller, E.; Fink, C.; Steidl-Müller, L. (Journal of Sport and Health Science, 2021)
Purpose: The study aimed to investigate the role of training load characteristics and injury and illness risk in youth ski racing. Methods: The training load characteristics as well as traumatic injuries, overuse injuries, and illnesses of 91 elite youth ski racers (age = 12.1+/-1.3 years, mean+/-SD) were prospectively recorded over a period of 1 season by using a sportspecific online database. Multiple linear regressionanalyses were performed to monitor the influence of training load on injuries and illnesses. Differences in mean training load characteristicsbetween preseason, in-season, and post-season were calculated using multivariate analyses of variance. Results: Differences were discovered in the number of weekly training sessions (p= 0.005) between pre-season (4.97+/-1.57) and post-season(3.24+/-0.71), in the mean training volume (p= 0.022) between in-season (865.8+/-197.8 min) and post-season (497.0+/-225.5 min) and in the mean weekly training intensity (Index) (p= 0.012) between in-season (11.7+/-1.8) and post-season (8.9+/-1.7). A total of 185 medical problems were reported (41 traumatic injuries, 12 overuse injuries, and 132 illnesses). The weekly training volume and training intensity was not a significant risk factor for injuries (p>0.05). Training intensity was found to be a significant risk factor for illnesses in the same week (ß= 0.348;p= 0.044; R2= 0.121) and training volume represents a risk factor for illnesses in the following week (ß= 0.397;p= 0.027; R2= 0.157). Conclusion: A higher training intensity and volume were associated with increased illnesses, but not with a higher risk of injury. Monitoring training and ensuring appropriate progression of training load between weeks may decrease incidents of illness in-season.